Linguopragmatic Research Of Craft Discourse (Texas Journal of Multidisciplinary Studies, 2025)
This article focuses on the linguopragmatic study of handicraft discourse. It examines communicative situations related to handicraft activities, the interaction between craftspeople, and the pragmatic strategies employed in presenting and selling their products. The study analyzes the specific pragmatic features of handicraft discourse, including speech acts, implicatures, politeness strategies, and discourse markers. The article discusses the socio-cultural context of handicraft discourse, its communicative goals, and its role in the relationships between craftspeople